2016
DOI: 10.1128/jb.00520-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Based Comparison of Cyclic Di-GMP Signaling in Pathogenic and Commensal Escherichia coli Strains

Abstract: The ubiquitous bacterial second messenger cyclic di-GMP (c-di-GMP) has recently become prominent as a trigger for biofilm formation in many bacteria. It is generated by diguanylate cyclases (DGCs; with GGDEF domains) and degraded by specific phosphodiesterases (PDEs; containing either EAL or HD-GYP domains). Most bacterial species contain multiples of these proteins with some having specific functions that are based on direct molecular interactions in addition to their enzymatic activities. Escherichia coli K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
71
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 79 publications
(112 reference statements)
0
71
0
Order By: Relevance
“…Genes involved in c-di-GMP signaling have also been studied in pathogenic E. coli, i.e., in uropathogenic E. coli (UPEC) (42), and two additional genes encoding PDEs have been detected in an enterohemorrhagic E. coli (EHEC) strain (38) and a meningitis-associated E. coli strain (39). Together with a recent analysis of genome sequences of 61 E. coli strains (29), which included commensal as well as pathogenic strains of the major pathotypes and phylogroups, a total of two additional GGDEF domain proteins and four more EAL domain proteins have been identified that are not found in E. coli K-12. On the basis of the presence of the key residues involved in enzymatic activities, these proteins should be active DGCs and PDEs (see an accompanying paper [29] in this issue).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Genes involved in c-di-GMP signaling have also been studied in pathogenic E. coli, i.e., in uropathogenic E. coli (UPEC) (42), and two additional genes encoding PDEs have been detected in an enterohemorrhagic E. coli (EHEC) strain (38) and a meningitis-associated E. coli strain (39). Together with a recent analysis of genome sequences of 61 E. coli strains (29), which included commensal as well as pathogenic strains of the major pathotypes and phylogroups, a total of two additional GGDEF domain proteins and four more EAL domain proteins have been identified that are not found in E. coli K-12. On the basis of the presence of the key residues involved in enzymatic activities, these proteins should be active DGCs and PDEs (see an accompanying paper [29] in this issue).…”
mentioning
confidence: 99%
“…However, on the basis of the finding that the DGC YdeH is regulated by zinc, it was recently renamed "DgcZ" (23). Also, the newly identified genes encoding DGCs and PDEs in non-K-12 E. coli strains had to be given names, and it seemed obvious to use a dgc and pde nomenclature (29).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An EAL-only-encoding gene, sfaY II , is part of a pathogenicity island in a newborn meningitis E. coli isolate and its expression in Vibrio cholerae has been shown to affect biofilm formation (37). Similar EAL-only proteins PdeW, PdeX, and PdeY have been found encoded in the genomes of various enteropathogenic and enterotoxigenic strains of E. coli (38).…”
mentioning
confidence: 99%